A 'geographer of the soul': James M. Houston's voyage from geography to theology. (2nd October 2022) - Philo, Chris
ABSTRACT: In the year of his 100th birthday, this contribution considers the unusual story of Scottish geographer James Macintosh Houston (1922-). Following his passage from undergraduate geographer at the University of Edinburgh to postdoctorate and then lecturer in geography at the University of Oxford, aspects of Houston's approach to geography – increasingly a cultural-historical geography, sometimes framed by him as the 'history of ideas' – are reconstructed. Narrating his dramatic change of career circa 1970, from academic geographer at Oxford to academic and practising theologian at Regent College, Vancouver, continuities are uncovered between Houston's geography and his theology. Particular attention is paid to his pioneering essay from 1978, the only one obviously directed back to geography from his new theological orbit, and one that should arguably be better-known as a profound statement of a humanistic geography critical of humanity becoming drawn into an abusive relationship with the world predicated on abstracted space rather than meaningful place(s). Drawing upon the example of Houston, reflections are offered on the relations between 'geographical theology' and 'theological geography'.